Corroles: The Hitherto Elusive Parent Macrocycle and its Metal Complexes. (20th October 2021) - Kumar, Amit; Yadav, Pinky; Majdoub, Mahmoud; Saltsman, Irena; Fridman, Natalia; Kumar, Sachin; Kumar, Anil; Mahammed, Atif; Gross, Zeev
Abstract: Corroles, macrocycles that owe their name to the cobalt‐chelating prosthetic group of vitamin B12 and share numerous features with the iron‐chelating porphyrin present in heme proteins/enzymes, constantly cross new boundaries ever since stable derivatives became easily accessible. Particularly important is the increasing utilization of corroles and the corresponding metal complexes for the benefit of mankind, in terms of new drug candidates for treating various diseases and as catalysts for sustainable energy relevant processes. One challenge is to gain access to the plain macrocycle, as to allow for full elucidation of the most fundamental properties of corroles. We have obtained the substituent‐free corrole by several surprising and conceptually different pathways. Selected features of the corresponding metal complexes are illuminated, for pointing towards unique phenomena that are anticipated to largely expand the horizon regarding their utilization for contemporary catalysis. Abstract : Three synthetic routes to the completely unsubstituted corrole are described. This allows for full characterization of five metal complexes chelated by this corrole, which were used to uncover unique beneficial features that are relevant to clean energy catalysis and many other purposes.